Field measurements of the interior and exterior aerodynamic pressure induced by a metro train passing through a tunnel. (February 2020) - Xiong, Xiaohui; Zhu, Liang; Zhang, Jie; Li, Aihua; Li, Xiaobai; Tang, Mingzan
Highlights: Field measurements have been conducted to study the aerodynamic pressure induced by a metro train passing through a tunnel. Influences of pressure changes on passenger's ear comfort have been analysed. Opening the airshaft leads to the increase of pressure outside and inside the metro train. A tunnel portal has a significant effect on the pressure outside and inside the metro train. Abstract: Aerodynamic effects (in particular the pressure variation) induced by the passage of a metro train in a tunnel intensify with the increase of train speed. When the interior pressure fluctuation of carriages exceeds limits, it may cause passengers' ear discomfort and even could cause serious injury. In this paper, field measurements have been used to study the influences of tunnel portals, airshafts and train speeds on the interior and exterior pressure variation of the metro train. The influence of pressure changes on passengers' ear comfort was also analysed in detail. The results show that the tunnel portal, the airshaft and the train speed are important factors that cause the fast pressure change inside and outside the metro train. When the airshaft is open, the interior and exterior aerodynamic pressure changes increase. The amplitudes of interior pressure variations of the metro train are dependent on running directions. From the entrance to the exit as defined, the amplitudes are approximately proportional to the train speed at a power exponent of 1.5–1.6, while changing the running direction those are approximately proportional to the train speed at a power exponent of 1.0–1.1. Additionally, when the metro train passes the tunnel interval with a clearance design diameter of 5.5 m at the speed of greater than 80 km/h and the tunnel interval includes a portal, it would pose a risk of passengers' ear discomfort. Thus, the running direction of the metro train should be considered in evaluating passengers' ear comfort.